Tārīkh-i Rashīdī - Dūghlāt, Mīrzā Muḥammad Ḥaydar, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islam, royal courts and other centers of wordly power played a major role in the survival and development of the sciences and the arts. And many rulers and high ranking officials themselves, too, often engaged in one or several of these. By way of example one may, for the Persianate world, mention Sultan Bayqārā (d. 911/1506), the Timurid ruler of Herat, and Ẓahīr al-Dīn Bābur (d. 937/1530), founder of the Mughal empire in India. Another example is the author of the present work, Mīrzā Muḥammad Ḥaydar Dūghlāt (d. 957/1551). Coming from a family of Chagatai generals and high administrators, he served a whole series of rulers in various parts of east Asia, mostly as a general and lastly as the ruler of Kashmir. Though wider in scope, the Tārīkh-i Rashīdī is above all a unique source of information on Chagatai history, full of personal reflexions on religion, culture, and the arts.